2018
DOI: 10.1103/physrevb.98.165435
|View full text |Cite
|
Sign up to set email alerts
|

Topological phonon polaritons in one-dimensional non-Hermitian silicon carbide nanoparticle chains

Abstract: Topological phonon polaritons (TPhPs) are highly protected and localized edge modes that are capable of achieving a strong confinement of electromagnetic waves and immune to impurities and disorder. Here we realize TPhPs by constructing one-dimensional dimerized silicon carbide nanoparticle chains, which mimic the topological property of the well-known Su-Schrieffer-Heeger (SSH) model. We analytically calculate the complex band structure of such chains by taking all nearfield and far-field dipole-dipole intera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 89 publications
(183 reference statements)
3
54
0
Order By: Relevance
“…which is related to the difference of the winding of the off-diagonal elements of the effective Hamiltonian around the origin. It is shown that although the present system is non-Hermitian and exhibits a breaking of chiral symmetry, the complex Zak phase is still quantized (only two values, 0 and π, are allowed) in a similar way as in a chirally symmetric system due to the fact that the eigenvectors are independent of the diagonal elements of the effective Hamiltonian [17,35,36]. According to Eq.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…which is related to the difference of the winding of the off-diagonal elements of the effective Hamiltonian around the origin. It is shown that although the present system is non-Hermitian and exhibits a breaking of chiral symmetry, the complex Zak phase is still quantized (only two values, 0 and π, are allowed) in a similar way as in a chirally symmetric system due to the fact that the eigenvectors are independent of the diagonal elements of the effective Hamiltonian [17,35,36]. According to Eq.…”
Section: Resultsmentioning
confidence: 91%
“…To see the localization behavior more clearly, here N = 2000 is used for the chain. We can find that for higher doping concentrations, the localization length of the topological edge modes become longer, which is a result of smaller interparticle dipole-dipole interactions [36]. To be more specific, with higher concentrations, the frequency of the topological modes becomes higher, leading to a shorter resonance wavelength.…”
Section: Doping Dependence Of Tppsmentioning
confidence: 83%
See 3 more Smart Citations